2005
DOI: 10.7589/0090-3558-41.4.792
|View full text |Cite
|
Sign up to set email alerts
|

A Serologic Survey for Antibodies to Three Canine Viruses in Wolverines (Gulo gulo) from the Brooks Range, Alaska

Abstract: Canine distemper virus (CDV), canine parvovirus type 2 (CPV-2), and canine adenovirus type 1 (CAV-1) are pathogens that are typically associated with canids but may cause serious disease in a wide range of other carnivores. From 1998 to 2002, serum samples from 64 wolverines (Gulo gulo) from the Brooks Range, Alaska, were tested for antibodies to CDV, CPV-2, and canine adenovirus (CAV). Four animals tested positive for antibodies to CDV (7%), one for antibodies to CPV-2 (2%), and none for antibodies to CAV. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Greene (1998) suggested that CAV can remain stable in the environment for long periods under cold conditions, which might partially explain the high prevalence on the Alaska Peninsula. Sympatric carnivores could also serve as reservoirs that perpetuate high CAV prevalence in wolves (Zarnke et al 1997;Dalerum et al 2005;Almberg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greene (1998) suggested that CAV can remain stable in the environment for long periods under cold conditions, which might partially explain the high prevalence on the Alaska Peninsula. Sympatric carnivores could also serve as reservoirs that perpetuate high CAV prevalence in wolves (Zarnke et al 1997;Dalerum et al 2005;Almberg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…data), the observed declines in prevalence could also indicate that conspecifics are not the primary source of infection. Sympatric carnivores could also serve as reservoirs for CCV (Foreyt and Evermann 1985;Dalerum et al 2005), and changes in their populations might also influence transmission rates. Additionally, CCV is environmentally labile and variation in CCV antibody Fall 17 (2/12) 100 (2/2) 0 (0/3) 0 (0/16) 9 (1/11) 0 (0/2) Spring -100 (15/15) 44 (4/9) 0 (0/12) 20 (1/5) 0 (0/7) Total 17 100 33 0 13 0 prevalence could also be related to varying environmental conditions during our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all harvested wolverines are registered. To gather population information on this population, 139 wolverine carcasses were salvaged from hunters from 1996 to 2003 (ranging from 2 carcasses/yr to 53 carcasses/yr; e.g., Dalerum 2005;Dalerum et al 2005Dalerum et al , 2007. Although this collection was not systematic enough to provide us with direct correction factors for official harvest statistics, when combined with official harvest statistics it allowed us to create likely boundaries for wolverine harvest in the area, which we set to vary from 10 animals/year to 100 animals/year.…”
Section: Population Model and Model Parametersmentioning
confidence: 99%
“…In the order Carnivora, six families are suspected of being susceptible to CPV: Felidae, Canidae, Procyonidae, Mustelidae, Ursidae, Ailuridae, and Viverridae [5]. Serological surveys in countries around the world report the high prevalence of CPV-2 in several species of captive and free-ranging wild carnivores [14][15][16][17]. In South American countries, including Brazil, serological studies show a high prevalence of antibodies against CPV-2 in this species [17][18][19].…”
Section: Introductionmentioning
confidence: 99%